2014
DOI: 10.1016/j.ijid.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of B-type natriuretic peptide for early risk prediction of infective endocarditis

Abstract: Among patients with IE, BNP levels obtained on admission provide incremental value for early and accurate risk prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In addition, Siciliano et al. 17 extended previous pilot studies to show that BNP was an independent predictor of in-hospital mortality in 104 patients with IE. However, the small sample size and lack of long-term follow-up limited the evidence of NT-proBNP for predicting poor outcomes in patients with IE.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, Siciliano et al. 17 extended previous pilot studies to show that BNP was an independent predictor of in-hospital mortality in 104 patients with IE. However, the small sample size and lack of long-term follow-up limited the evidence of NT-proBNP for predicting poor outcomes in patients with IE.…”
Section: Discussionmentioning
confidence: 85%
“…The largest sample was 104 patients. 17 In addition, the outcomes of these studies were limited to in-hospital. The impact of NT-proBNP on long-term outcomes in patients with IE remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study among 50 patients, Cornelissen et al 21 found leukocytosis, elevated C-reactive protein (CRP) levels and elevated procalcitonin as independent predictors of complications. Other predictors that have been studied and found useful include brain-type natriuretic peptide (BNP) levels, 22 neutrophil-to-lymphocyte ratio, 23 D-dimer levels 24 and mean platelet volumes 25 . Although serial monitoring of CRP levels is proven to have a role in predicting treatment outcomes, the value of CRP level at admission has been scantily studied 26, 27, 28.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported lower prevalence rates compared to the current study. For example, in Brazil, only 2.06% isolates contained blaNDM, and 0.72% blaVIM [27]. In another study, of 170 K. pneumoniae clinical isolates four became positive for blaNDM [28].…”
Section: Vol 8 Nomentioning
confidence: 96%